CorSalud en la Biblioteca Científica Electrónica en Línea: SciELO - Gil Hernández, Tunia; Hernández de la Rosa, Yurima; Rodríguez Camacho, Osmani; Benítez Pérez, María O. (CorSalud, 2018)
CorSalud en la Biblioteca Científica Electrónica en Línea: SciELO